Comparative mutational analysis of the Zika virus genome from different geographical locations and its effect on the efficacy of Zika virus-specific neutralizing antibodies - Aziz, Abdul; Suleman, Muhammad; Shah, Abdullah; Ullah, Ata; Rashid, Farooq; Khan, Sikandar; Iqbal, Arshad; Luo, Sisi; Xie, Liji; Xie, Zhixun (Frontiers in Microbiology, 2023)
Originating in Africa, the Zika virus (ZIKV) has spread to many parts of the globe and become one of the major threats to human health worldwide. Being an RNA virus, the Zika virus continues to mutate and accumulate multiple mutations within its genome. Some of these mutations act as a primary driving force to alter the virus’s infectivity, virulence, transmissibility, immune system modulation, and drug resistance. In this study genome-wide analysis of 175 zika virus isolates deposited at the National Center for Biotechnology Information (NCBI), were carried out. The comprehensive mutational analysis of these isolates revealed 257 different substitutions at the proteome level in different proteins when compared to the reference sequence (KX369547.1). The substitutions were capsid (17/257), preM (17/257), envelope (44/257), NS1 (34/257), NS2A (30/257), NS2B (11/257), NS3 (37/257), NS4A (6/257), 2K (1/257), NS4B (15/257), and NS5 (56/257). Based on the coexisting mutational analysis, the MN025403.1 isolate from Guinea was identified as having 111 substitutions in proteins and 6 deletions. The effect of coexisting/reoccurring mutations on the structural stability of each protein was also determined. Furthermore, molecular dynamics simulation results showed that the coexisting mutations (I317 V and E393D) in Domain III (DIII) of the E protein enhanced the bonding network with ZIKV-specific neutralizing antibodies. This study, therefore, highlighted the rapid accumulation of different substitutions in various ZIKV proteins circulating in different geographical regions of the world. Surveillance of such mutations in the respective proteins will be helpful in the development of effective ZIKV vaccines and neutralizing antibody engineering.